Book Review: A VOICE IN THE FOREST: CONVERSATIONS WITH ALEX SANDERS - Clifton, Chas S (Pomegranate, 2000)
Although it is written for a narrowly defined audience, A Voice in the Forest should interest anyone concerned with issues of mediumship and the establishment of what are sometimes called magical “contacts” within revived Witchcraft.